The role of brand image and brand trust in mediating the influence of e-WOM on purchase decision (case of video-on-demand Netflix) - Natasya Stefanny; Filda Rahmiati; Mastura Roni (IDEAS: Journal of Management & Technology, 2022)
It is now evident that technology is progressing at a rapid rate around the globe. Due to the significance of technology, our lives have become entirely digital. Streaming has gained popularity owing to its accessibility, as opposed to viewing television or movies on a huge screen. This presents an opportunity for SVoD services to compete, beginning with practical issues such as the amount of money that must be spent and shifting lifestyle habits. Subscription Video on Demand, or SVoD, is a service that allows anyone to view as many television programs as they choose for a monthly fee. E-WOM is the independent variable, purchase decision is the dependent variable, and brand image and brand trust are the mediating factors. This research distributes questionnaires using a quantitative approach, non-probability sampling, and the snowball sampling method, and is processed with SmartPLS 3.3.7. (Partial Least Square-Structural Equation Model). The total number of Indonesian participants in this study is 148. The findings indicates that E-WOM has a major impact on buying choice, brand trust, and brand image. Additionally, brand image and brand trust have a substantial impact on purchasing decisions. Consequently, E-WOM has a substantial impact on purchasing decisions mediated through brand trust and brand image.